2015
DOI: 10.4137/bmi.s29514
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Current Efforts in the Development of Biomarkers for Chronic Inflammatory and Remodeling Conditions of the Lungs

Abstract: This review discusses biomarkers that are being researched for their usefulness to phenotype chronic inflammatory lung diseases that cause remodeling of the lung’s architecture. The review focuses on asthma, chronic obstructive pulmonary disease (COPD), and pulmonary hypertension. Bio-markers of environmental exposure and specific classes of biomarkers (noncoding RNA, metabolism, vitamin, coagulation, and microbiome related) are also discussed. Examples of biomarkers that are in clinical use, biomarkers that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 319 publications
(370 reference statements)
0
4
0
Order By: Relevance
“…From the point of view of pathophysiological process, asthma is considered as chronic inflammation of the respiratory tract, regulated by various cellular elements and inflammatory mediators (8). The development of chronic inflammation of the bronchopulmonary system is due in no small part to vascular and endothelial factors (9). The cascade of inflammatory reactions is determined by the activation of the endothelium, which expresses on its surface molecules of intercellular adhesion (in particular, sVCAM-1), resulting in the processes of migration of effector cells and tissue infiltration and vascular inflammation (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the point of view of pathophysiological process, asthma is considered as chronic inflammation of the respiratory tract, regulated by various cellular elements and inflammatory mediators (8). The development of chronic inflammation of the bronchopulmonary system is due in no small part to vascular and endothelial factors (9). The cascade of inflammatory reactions is determined by the activation of the endothelium, which expresses on its surface molecules of intercellular adhesion (in particular, sVCAM-1), resulting in the processes of migration of effector cells and tissue infiltration and vascular inflammation (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it can be assumed that the degree of endothelial dysfunction may be associated with the severity of the disease (15,16). It is believed that thorough determination of vascular and endothelial factors in the development of chronic inflammatory process of the bronchopulmonary system may be one of the perspective directions of further scientific study of the mechanisms of development, formation, and progression of asthma (9). Thus, in our study, we aimed to evaluate the endothelial function in children with asthma in remission and the prognosis of severe asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical features, hemodynamic parameters, echocardiography patter, multi-spiral computer tomography findings, exercise capacity, and anti-nuclear antibody profiles were found as powerful factors predicted a development of PAH due to several diseases [8], the reliability, sensitivity, specificity and predictive value are derived from PAH patients with different comorbidities and specific complications associated with CTD, congenital heart disease and respiratory disease might be unacceptable [9]. In this context, taken into consideration pathophysiological heterogeneity of PAH to risk stratification based on biological markers (N-terminal pro-brain natriuretic peptide, red cell distribution width, soluble endoglin, growth differentiation factor-15, interleukin-6, soluble vascular endothelial growth factor receptor-1, C-reactive protein, pentraxin 3) reflected several faces of nature evolution of the disease might be useful and appears to be attractive [10][11][12][13]. Recent pre-clinical and clinical studies have been indicated an important role for Galectin-3 (Gal-3) signaling mechanism in the pathophysiology of IPAH and PAH-CTD [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical features, hemodynamic parameters, echocardiography patter, multi-spiral computer tomography findings, exercise capacity, and anti-nuclear antibody profiles were found as powerful factors predicted a development of PAH due to several diseases [8], the reliability, sensitivity, specificity and predictive value are derived from PAH patients with different comorbidities and specific complications associated with CTD, congenital heart disease and respiratory disease might be unacceptable [9]. In this context, taken into consideration pathophysiological heterogeneity of PAH to risk stratification based on biological markers (N-terminal pro-brain natriuretic peptide, red cell distribution width, soluble endoglin, growth differentiation factor-15, interleukin-6, soluble vascular endothelial growth factor receptor-1, C-reactive protein, pentraxin 3) reflected several faces of nature evolution of the disease might be useful and appears to be attractive [10][11][12][13]. Although several biomarkers are widely investigated for risk stratification around patients with PAH, there are several limitations to clinical use associating with higher biological variability and cost, low specificity, lack direct evidence regarding prediction of clinical status and outcomes.…”
Section: Introductionmentioning
confidence: 99%